DEVELOPMENT OF STUDENT NEEDS ASSESSMENT GUIDELINES IN PLANNING GUIDANCE AND COUNSELING PROGRAMS - Romiaty; Apriatama, Dony; Pangestie, Esti Pan; Stevandy, Matias (CV. TOTUS TUUS, 2024)
The Coronavirus Disease 2019 (Covid-19) pandemic has necessitated the adaptation of daily life, including education, to coexist with the virus, commonly termed the